GAMBARAN PENGGUNAAN SOSIAL MEDIA PADA SISWA SEKOLA MENENGAH ATAS - Aulia Ramadhani Ibrahim; Euis Eti Rohaeti; Maya Masyita Suherman (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2020)
Social media provides many conveniences that can be obtained from cellphones and the internet, almost all people are users of technology and information and prove that at this time life cannot be separated from technology and information. This study aims to describe the use of social media among high school students. The approach used by researchers is descriptive qualitative, data collection is done by interview and observation. The subjects of this study were a counseling teacher and two students of SMA Negeri 1 Batujajar. The results found that social media affects teaching and learning activities in schools. Keywords: Social Media, Teenager.